Analisis Multidimensi Keberlanjutan Usahatani Padi Sawah: Studi Kasus di Desa Ponoragan, Kecamatan Loa Kulu, Kabupaten Kutai Kartanegara - Arief, Akhmad; Dwijatenaya, Ida Bagus Made Agung; Handayani, Pinto Rukmi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Loa Kulu Subdistrict is one of the centers of agricultural production in Kutai Kartanegara Regency. In recent years, agricultural production has decreased due to several factors, including the conversion of agricultural land, climate change, limited access to agricultural technology, and uncertainty in farmers' welfare. Sustainable agriculture aims to provide food for the increasing food needs without environmental damage. The purpose of the study was to determine the sustainability status of paddy rice farming in Ponoragan Village and to determine the attributes that have sensitivity. The research used a descriptive quantitave approach with a purposive sampling technique with eleven key informants in this study. Data analysis using multidimensional scaling with RAPFARM software. The results of the research on paddy rice farming in Ponoragan Village have a multidimensional value of 43.90% (Less Sustainable). The social dimension is categorized as sustainable, while the economic, ecological, technological, and institutional dimensions are less sustainable. The economic dimension has three sensitive attributes, namely marketing structure, land ownership, and farmer profits. The ecological dimension has two sensitive attributes, namely chemical input dependency and irrigation. The social dimension has one sensitive attribute, namely farmer education level. The technological dimension has one sensitive attribute, namely the response to technology. And the institutional dimension has one sensitive attribute, namely subsidy assistance.